Artificial multiferroic structures using soft magnetostrictive bilayers on Pb(Mg1/3Nb2/3)–PbTiO3. (1st February 2018) - Miskevich, E; Alshammari, F K; Yang, W-G; Sharp, J; Baco, S; Leong, Z; Abbas, Q A; Morley, N A
Abstract: Artificial multiferroic structures are of great interest as they combine two or more functionalities together. One example of these structures is magnetostrictive films grown on top of piezoelectric substrates; allowing the magnetisation hysteresis loop of the magnetostrictive film to be manipulated using an electric field across the structure rather than a magnetic field. In this paper, we have studied the multiferroic structure NiFe/FeCo/Ti/Pb(Mg1/3 Nb2/3 )–PbTiO3 (PMN-PT) as a function of the electric and magnetic field. Soft magnetostrictive bilayer films (NiFe/FeCo) are studied, as often applications require soft magnetic properties (small coercive and anisotropy fields) combined with larger magnetostrictive constants. Unfortunately, FeCo films can have coercive fields that are too large, while NiFe films' magnetostriction constants are almost zero; thus, combining the two together should produce the 'ideal' soft magnetostrictive film. It was found that the addition of a thin NiFe film onto the FeCo film reduced the coercive field and remnant magnetisation on the application of an applied voltage in comparison to just the FeCo film. It was also determined that for the NiFe/FeCo bilayer the magnetisation switchability was 100% on the application of 8 kV cm −m, which was higher than the monolayer FeCo films at the same applied field, demonstrating improvement of the multiferroic behaviour by the soft magnetic/magnetostrictive bilayer.